Incidence and prevalence of neurodevelopmental disorders and disabilities among métis children in Alberta, Canada: A retrospective birth cohort study - Stuart Lau; Jesus Serrano-Lomelin; Matt Hicks; Reagan Bartel; Kelsey Bradburn; Ashton James; Susan Crawford; Jeffrey A. Bakal; Amy Colquhoun; Anne Hicks; Manoj Kumar; Rhonda J. Rosychuk; et al. (PLoS ONE, 2025)
Limited research has examined the neurodevelopmental health of Métis children from a functional perspective, which is essential for culturally sensitive service planning, and policy development. This population-based retrospective birth cohort study linked provincial administrative health data of Métis and non-Métis singleton live births (2006–2016) to follow them up to 10 years of age. A random 1:4 sample of non-Métis children served as a reference group. Neurodevelopmental disorders and disabilities (NDD/D) were examined across six functional NDD/D domains. Prevalence odds ratios (pOR) with 95% confidence intervals (CI) were calculated using logistic regression models, adjusted for maternal and neonatal characteristics. Incidence rates (IR) per 1,000 person-years were estimated, and age-specific IR was modeled using longitudinal Poisson regression, adjusting for covariates. Associations between maternal and neonatal characteristics and NDD/D incidence among Métis children were examined using multivariable longitudinal Poisson regression models, with adjusted incidence rate ratios (IRR) and 95% CI reported. A total of 38,958 singleton live births were included (7,853 Métis and 31,105 non-Métis). Overall NDD/D prevalence among Métis (3.3%) and non-Métis (2.8%) children did not differ significantly after adjustment (adjusted pOR: 1.1, 95% CI: 0.9, 1.3). Learning-cognition was the most prevalent NDD/D domain. Métis children had a higher IR of NDD/D at age 2 (5.5 vs. 2.8 cases per 1,000 person-years, rate difference: 2.7 [95% CI: 0.8, 4.6]). Among Métis children, higher NDD/D incidence was associated with maternal age younger than 20 or older than 35 years, high pre-pregnancy weight, male sex, preterm birth, and congenital anomalies. While overall NDD/D prevalence was similar between Métis and non-Métis children, Métis children were more likely to be diagnosed at age 2, suggesting potential differences in early diagnosis, access to care, or underlying risk factors. A functional classification approach of neurodevelopmental health supports culturally responsive early screening and intervention strategies to address these differences.